Characterization of SARS-CoV-2 nucleocapsid protein reveals multiple functional consequences of the C-terminal domain - Chao Wu; Abraham J. Qavi; Asmaa Hachim; Niloufar Kavian; Aidan R. Cole; Austin B. Moyle; Nicole D. Wagner; Joyce Sweeney-Gibbons; Henry W. Rohrs; Michael L. Gross; J. S. Malik Peiris; Christopher F. Basler; et al. (iScience, 2021)
Summary: Nucleocapsid (N) encoded by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) plays key roles in the replication cycle and is a critical serological marker. Here, we characterize essential biochemical properties of N and describe the utility of these insights in serological studies. We define N domains important for oligomerization and RNA binding and show that N oligomerization provides a high-affinity RNA-binding platform. We also map the RNA-binding interface, showing protection in the N-terminal domain and linker region. In addition, phosphorylation causes reduction of RNA binding and redistribution of N from liquid droplets to loose coils, showing how N-RNA accessibility and assembly may be regulated by phosphorylation. Finally, we find that the C-terminal domain of N is the most immunogenic, based on antibody binding to patient samples. Together, we provide a biochemical description of SARS-CoV-2 N and highlight the value of using N domains as highly specific and sensitive diagnostic markers.